Addressing Educational Disparities in the Philippines: An Examination of the Impact of Alternative Delivery Modes (ADMs) on Achieving Inclusive and Quality Education - Ladines, Teresa Gayle (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2023)
The United Nations established seventeen Sustainable Development Goals (SDGs) in 2015, and nearly every country, including the Philippines, pledged to pursue them. Among these goals is SDG 4, which aims to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. Recognized as a fundamental human right, the attainment of quality education extends beyond mere accessibility. Unfortunately, the Philippines continues to grapple with providing inclusive high-quality education to its populace. This study undertakes a thematic analysis of data gathered from previous studies and literary works to analyze the impacts of alternate delivery modalities (ADMs) in the Philippines' pursuit of inclusive and high-quality education. Specifically, the research explores the perspectives of parents, teachers, and students on various aspects of ADMs, seeking to shed light on their effectiveness in addressing educational disparities. The findings of the study bring to the forefront significant challenges associated with the integration of ADMs in the educational landscape. Among these obstacles are the inadequacy of essential resources, limited teacher communication, and an increased workload that places emotional strain on teachers. These difficulties have notable implications for student motivation, interest, and overall learning outcomes, particularly for students coming from low-income backgrounds. Addressing these urgent concerns and adhering to the SDG 4 targets for 2030, this research provides tangible recommendations and viable solutions. By acknowledging and actively tackling the challenges that ADMs face, the Philippines may get closer to attaining its goal of delivering inclusive and high-quality education to all its residents.